GAMBARAN ALAT PERMAINAN EDUKATIF “PAPAN HITUNG” DALAM MENGEMBANGKAN KEMAMPUAN BERHITUNG ANAK USIA 5-6 TAHUN DI KB/TK ISLAM AL-JABBAR MALANG - Nur Vitria Sari, Pradita Desti; Ahmad Fachrurrazi (LPPM IAD Probolinggo, 2025)
The ability to count is very important in the cognitive development of young children. Unfortunately, many children aged 5 to 6 years struggle to understand the basics of mathematics. This problem often arises due to the lack of engaging learning tools and teaching methods that are not suitable for the nature and developmental needs of the child. This study aims to describe how effective educational game tools in the form of counting boards are in helping children aged 5 to 6 years learn to count. The method used is descriptive qualitative, with 5 children from the Al-Jabbar Islamic Kindergarten in Malang selected using purposive sampling techniques. The data was collected through observation, interviews, and documentation, and then analyzed using triangulation techniques. Findings from the research indicate that the use of counting boards regularly can improve children's understanding of addition and subtraction, accelerate problem-solving, and increase children's confidence when counting. The results of this study emphasize the importance of using concrete, enjoyable tools that are appropriate for children's cognitive development stages as an effective strategy in early childhood education. Keywords: Children's Numeracy Skills; Children 5-6 Years Old; Educative Game Tools